Dynamic Behavior of Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue on the “Dynamic Behavior of Materials” collected recent research findings on the dynamic behavior of various materials. A collection of fifteen peer-reviewed research articles were included in this Special Issue. The main topics covered include processing technology, state-of-the-art characterization, testing, theoretic modeling, and simulation. We hope that this Special Issue will be interesting for the academic community, and also hope that it will shed light on future research activities in this field.